2018
DOI: 10.1159/000494431
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Onset Diabetes of the Young due to Glucokinase, HNF1-A, HNF1-B, and HNF4-A Mutations in a Cohort of Turkish Children Diagnosed as Type 1 Diabetes Mellitus

Abstract: Background/Aims: Maturity onset diabetes of the young (MODY) is a rare condition often misdiagnosed as type 1 diabetes (T1D). The purposes of this study were: to identify any patients followed in a large Turkish cohort as T1D, with an atypical natural history, who may in fact have MODY, and to define the criteria which would indicate patients with likely MODY as early as possible after presentation to allow prompt genetic testing. Methods: Urinary C-peptide/creatinine ratio (UCPCR) was studied in 152 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…1 It is reported that urinary C-peptide measurements will also be used as a marker for MODY screening. 23 T A B L E 5 HNF4A, HNF1A The most common cause of MODY globally and in Turkey is mutations in the GCK gene. 11,24 Otherwise, mutations in the HNF1A gene is the most common cause in some countries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 It is reported that urinary C-peptide measurements will also be used as a marker for MODY screening. 23 T A B L E 5 HNF4A, HNF1A The most common cause of MODY globally and in Turkey is mutations in the GCK gene. 11,24 Otherwise, mutations in the HNF1A gene is the most common cause in some countries.…”
Section: Discussionmentioning
confidence: 99%
“…4 MODY is often misdiagnosed as type 1 (T1DM) or type 2 diabetes mellitus (T2DM). 5 Unlike the obvious clinical signs in T1DM and T2DM, MODY mostly presents with hidden or mild findings. Molecular analyses that make a definitive diagnosis are expensive and may not always be available and clinical manifestations gradually appear over a long period of time.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations